PAMAM-Lys, a Novel Vaccine Delivery Vector, Enhances the Protective Effects of the SjC23 DNA Vaccine against Schistosoma japonicum Infection - Wang, Xiaoting (Public Library of Science, 2014)
BACKGROUND: Schistosomiasis japonica remains a major public-health concern in China. Praziquantel-based chemotherapy effectively reduces both infections and intensity; however, it can not prevent re-infection. Furthermore, there is an increasing concern about praziquantel resistance following long-term repeated use of the drug in endemic areas. Therefore, development of a schistosomiasis vaccine, as a strategy to prevent and control schistosomiasis japonica, has been given high priority. The present study was conducted to develop PAMAM dendrimers as a novel vaccine delivery vector for a schistosomiasis japonica DNA vaccine and evaluate its ability to enhance protective effects against Schistosoma japonicum infection. METHODOLOGY/PRINCIPAL FINDINGS: Lysine was used to modify 4.0G PAMAM, and the modified product PAMAM-Lys was synthesized. PAMAM-Lys showed both high transfection and low cytotocity for gene delivery in vitro. DNA vaccines combined with PAMAM-Lys produced higher level of protection compare with naked DNA vaccines against S. japonicum infection in a mouse model. Futhermore,antibodies from mice immunized with PAMAM-Lys combined DNA vaccines were significantly higher than those of mice immunized with the naked DNA vaccines. The PAMAM-Lys vector elicited a predominantly IgG2a antibody response and a tremendously increase in the production of IL-2 and IFN-γ. CONCLUSION/SIGNIFICANCE: Lysine-modified PAMAM-Lys is an excellent vector. PAMAM-Lys may enhance the immunoreactivity of DNA vaccine and increase the protective effect of the SjC23 DNA vaccine against S. japonicum infection.